Assessment of the knowledge and awareness of a sample of young researcher physicians on reporting guidelines and the EQUATOR network: A single center cross-sectional study - YAĞCI, İLKER; KARACAATLI, MELTEM; GÜNDÜZ, OSMAN HAKAN; KENİŞ COŞKUN, ÖZGE (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: This study aimed to investigate knowledge and awareness of a sample of young researcher physicians about reporting guidelines and the EQUATOR network. Materials and Methods: One hundred young researcher physicians were enrolled for the study and evaluated using a questionnaire which assessed the level of usage and knowledge of reporting guidelines and the EQUATOR network. Results: Thirty-eight percent of the participants were aware of the EQUATOR network The most recognized reporting guidelines were CONSORT (32%), PRISMA (35%), and the least recognized ones were ARRIVE (12%) GRRAS (12%). The percentage of participants who were aware of the EQUATOR network and reporting guidelines were deficient. Seventy-three percent of the participants declared that they requested more information about reporting guidelines when they were asked whether they wished to be informed about reporting guidelines. There were statistically significant differences between specialists and residents regarding the level of knowledge on reporting guidelines and reporting guideline use except for PRISMA and SAMPL guidelines and their level of the desire to be informed about guidelines were similar. When participants whose publication number was above and below the mean of publications of all participants were compared, the level of reporting guidelines usage and knowledge of PRISMA, GRRAS were similar and both groups showed equal levels of desire to be informed about guidelines. Conclusion: The use and awareness of the EQUATOR network and reporting guidelines are low among young researcher physicians. To improve the quality of manuscript writing and the acceptance rates, knowledge and awareness of the EQUATOR network and reporting guidelines should be increased among young physicians doing research.
Keywords: EQUATOR network; Reporting guidelines; Research; TRANSPARENT; ACCURATE